The health of HIV-exposed children after early weaning - Parker, Megan E.; Tembo, Martin; Adair, Linda; Chasela, Charles; Piwoz, Ellen G.; Jamieson, Denise J.; Ellington, Sascha; Kayira, Dumbani; Soko, Alice; Mkhomawanthu, Chimwemwe; Martinson, Francis; van der Horst, Charles M.; et al. (Wiley, 2013)
There are potential health risks associated with the use of early weaning to prevent mother‐to‐child transmission of human immunodeficiency virus (HIV) in resource‐poor settings. Our objective was to examine growth and nutrient inadequacies among a cohort of children weaned early. Children participating in the Breastfeeding Antiretrovirals and Nutrition (BAN) Study in Lilongwe, Malawi, had HIV‐infected mothers, were weaned at 6 months and fed LNS until 12 months. 40 HIV‐negative, BAN‐exited children were compared with 40 HIV‐negative, community children matched on age, gender and local health clinic. Nutrient intake was calculated from 24‐h dietary recalls collected from BAN‐exited children. Anthropometric measurements were collected from BAN‐exited and matched community children at 15–16 months, and 2 months later. Longitudinal random effects sex‐stratified models were used to evaluate anthropometric differences between the two groups. BAN‐exited children consumed adequate energy, protein and carbohydrates but inadequate amounts of fat. The prevalence of inadequate micronutrient intakes were: 46% for vitamin A; 20% for vitamin B6; 69% for folate; 13% for vitamin C; 19% for iron; 23% for zinc. Regarding growth, BAN‐exited girls gained weight at a significantly lower rate {0.02 g kg−1 per day [95% confidence interval (CI): 0.01, 0.03]} than their matched comparison [0.05 g kg−1 per day (95% CI: 0.03, 0.07)]; BAN girls grew significantly slower [0.73 cm month−1 (95% CI: 0.40,1.06)] than their matched comparison (1.55 cm month−1[95% CI: 0.98, 2.12]). Among this sample of BAN‐exited children, early weaning was associated with dietary deficiencies and girls experienced reduced growth velocity. In resource‐poor settings, HIV prevention programmes must ensure that breastfeeding stop only once a nutritionally adequate and safe diet without breast milk can be provided.